2020
DOI: 10.1097/ana.0000000000000744
|View full text |Cite
|
Sign up to set email alerts
|

Early Lymphopenia and Infections in Nontraumatic Subarachnoid Hemorrhage Patients

Abstract: Introduction: Subarachnoid hemorrhage (SAH) is associated with high morbidity and mortality. A certain degree of immunodepression has been reported during critical illness, and lymphopenia identified as an independent predictor of poor outcome; no data are available for critically ill SAH patients. We aimed to evaluate the prevalence of lymphopenia among SAH patients and its association with hospital-acquired infection.Methods: Retrospective cohort study of adult patients admitted to an intensive care unit wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…[29][30][31] Decreased serum lymphocytes plays a role in infectious complications of aSAH, although the association with vasospasm is unclear. 31,32 Elevated NLR independently predicts DND and functional outcome, although predictive ability for vasospasm has not been fully established. 14,33,34 Further, evidence supports the role of platelet activation in driving poor outcomes after aSAH.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] Decreased serum lymphocytes plays a role in infectious complications of aSAH, although the association with vasospasm is unclear. 31,32 Elevated NLR independently predicts DND and functional outcome, although predictive ability for vasospasm has not been fully established. 14,33,34 Further, evidence supports the role of platelet activation in driving poor outcomes after aSAH.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that 15.8–41% of CNS injury patients contracted nosocomial infections during hospitalization [ 20 , 21 , 22 , 23 ]. Increased infection risk (31% vs. 17%) was observed among patients with non-traumatic SAH, with lymphopenia reported among 45% of the patients [ 24 ]. The inflammatory cytokine surge may contribute to the immunosuppressed state [ 25 , 26 ] after aSAH by promoting the secretion of corticotropin-releasing hormone (CRH) from the hypothalamic paraventricular nucleus (PVN) [ 27 , 28 , 29 , 30 ].…”
Section: Neuroimmune Axes In Asahmentioning
confidence: 99%
“…According to a large retrospective cohort study, lymphopenia increases the risk of infection and infectionrelated death in the general population (6). In patients with sepsis, lymphopenia is associated with increased mortality, and dynamic lymphocyte decline is also associated with poor prognosis (7)(8)(9)(10). Nevertheless, due to the heterogeneity of critically ill patients, there are also differences in ALC; for example, ALC at admission to ICU is lower in elderly patients than in non-elderly patients (11).…”
Section: Introductionmentioning
confidence: 99%